Forecasting monetary policy in Switzerland: Some empirical assistance - Thorsten Hock; Patrick Zimmermann (University of Würzburg, Department of Economics, 2005)
This paper provides empirical assistance in forecasting monetary policy in Switzerland. After the introduction, we provide a descriptive analysis of the four cycles of rising interest rates from 1979 to 2003. It is apparent that the individual cycles diverge to greater or lesser degrees from the average rising interest rate cycle. The third section evaluates the quality of various market forecasts. Regardless of the method of measurement, they show statistically significant and systematic forecast errors. Even simple trend forecasts for money market rates seldom beat the toss of a coin. If we divide the observation periods into regimes of rising and of falling interest rates, then forecasts based on futures contracts on the 3-month LIBOR are superior to other market variables such as forwards or consensus estimates in times when rates are rising. In the fourth section, we assess an empirical response function for the Swiss National Bank's (SNB) monetary policy. Due to the long, variable time lags with which monetary policy affects the real economy, the central banks must adopt a forward-looking approach and base decisions on expectations. Hence by employing consensus forecasts, we use expectations for inflation and growth as explanatory variables. The analysis shows that the SNB has a stable interest rate policy, with inflation forecasts weighted four times more heavily than growth expectations. Assuming the SNB will behave similarly in the future as it did in the past, this rule of thumb allows us to assign historically consistent money market rates to a specific macro-economic climate.
Keywords: 330; Geldpolitik; Prognoseverfahren; Schweiz